Optimization design of the cathode flow channel for proton exchange membrane fuel cells. (1st September 2018) - Fan, Linhao; Niu, Zhiqiang; Zhang, Guobin; Jiao, Kui
Highlights: Two novel PEMFC cathode channel designs are proposed and investigated in detail. Air-guide plates of 30°, 0.5 mm width and 6.0 mm distance exhibit best performance. Effect of air-guide plates' angle on PEMFC performance is most significant. The novel channels can facilitate the reactant supply and liquid water removal. Maximum improvement of cell net power for novel channels are 4.7% and 7.5%. Abstract: Two novel cathode channel designs (multi-plates structure channel and integrated structure channel) are proposed and investigated by a three-dimensional multiphase numerical model. The numerical results indicate that the PEMFC with 30° angle, 0.5 mm width and 6.0 mm distance of air-guide plates exhibits the best performance, and the effect of plates angle on PEMFC performance is most significant. Compared with the conventional channel, the novel channel designs are found to be capable of forcing more oxygen towards cathode catalyst layer (CCL) to improve the electrochemical reaction rate. In addition, these two novel channel designs are able to remove more liquid water from PEMFC to effectively avoid from water flooding. According to the simulation results, the maximum improvement of PEMFC net power densities for the multi-plates structure and integrated structure are 4.7% and 7.5%, respectively.